Kongress russkikh obshchin . Kongress russkikh obshchin . Congress of Russian Communities . Конгресс русских общин - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Report on the Second World Congress of Russian Communities. Featured in the program: Kovalev, Sergei (Human Rights Attorney of the Russian Federation); Grachev, Pavel Sergeevich (Defense Minister of the Russian Federation) Репортаж о Втором Всемирном Конгрессе русских общин. В программе участвуют: Ковалев, Сергей (Уполномоченный по правам человека Российской Федерации); Грачев, Павел Сергеевич (Министр обороны Российской Федерации)